Chronic pyelonephritis in children. - Axmadjanov Furkat Ilyos o’g’li (Peerian Journals Publishing, 2023)
Chronic pyelonephritis in children is a condition characterized by persistent renal inflammation and scarring resulting from recurrent urinary tract infections (UTIs). This article delves into the complexities of chronic pyelonephritis, exploring its impact on pediatric renal health. Through a comprehensive literature analysis, the article aims to provide insights into the etiology, diagnostic methods, and management strategies, emphasizing the importance of early intervention to mitigate long-term complications.
Keywords: Chronic pyelonephritis; children; renal infections